PERBANDINGAN ANALISIS PERAMALAN DOUBLE EXPONENTIAL SMOOTHING DAN TRIPLE EXPONENTIAL SMOOTHING PADA INDEKS HARGA KONSUMEN DI YOGYAKARTA - Lazuardy Ilham Effendie; Utami Putri Wysnawati; Qurratul Ainunnisa (LPPM Universitas Bina Bangsa, 2023)
The Consumer Price Index, commonly known as the CPI, is an index derived from calculating the average price change of a good and service in a period consumed by the population for a certain period of time. The CPI is a vital indicator used in calculating inflation, and inflation plays an important role in the economy. Thus, the CPI movement greatly affects the cost of living needed by each citizen for goods and services consumed and can provide an overview of inflation or deflation. This paper aims to provide a future picture to the government to provide an upcoming policy and show that it needs special attention for all circles. The data used in this research is the CPI in DI Yogyakarta from January 2012 to April 2022. The CPI data from January 2012 to April 2022 is forecasted using two methods, namely Double Exponential Smoothing and Triple Exponential Smoothing. MSE (Mean Square Error) and MAPE (Mean Absolute Percentage Error). Then the two methods are compared, and the best method is Double Exponential Smoothing with the MAPE value is 0.976, the MAPE value <10% means that forecasting with Double Exponential Smoothing can be said to be good and can be used